Effects of Cadmium Chloride on Isolated Rat Hepatocytes - Chinaratanavech, Pornpimol; Pramyothin, Pornpen (Journal of Basic and Applied Pharmacology, 2015)
The cytotoxic effects of cadmium chloride was studied in isolated rat hepatocytes. Cadmium chloride appeared to have the direct toxic effects on plasma membrane integrity as shown by the leakage of cytoplasmic enzymes and intracellular potassium. The metabolic capability of isolated cells was also affected by cadmium chloride. There was the sign of inhibition on carbohydrate metabolism especially the gluconeogenesis. These toxic effects of cadmium chloride were dose-related and could be detected as early as 30 minutes of incubation.